(untitled) (Third Sector Social Economic Review, 2025)
In this study, the long-term relationships between trade openness (exports + imports/GDP), direct foreign investment (DFI), inflation rates, and economic growth over the period 1990-2023. Empirical findings indicate the existence of long-term cointegration relationships between the trade balance and the aforementioned macroeconomic variables. According to the moments method based on panel cantilever regression analysis, DYY has been found to have a statistically significant and negative effect in reducing the trade gap across all cantilevers. This effect is particularly pronounced in quantiles where the trade balance is low. Furthermore, it was found that the effect of inflation rates on the trade deficit is stronger in lower quantiles and diminishes as one moves to higher quantiles, while the effect of economic growth is inversely related, being weaker at low levels of the trade deficit and stronger at high levels.